Internal Social Media and Turnover Intention in Indonesia: The Moderation Role of Toxic Leadership - Andrias, Mone Stepanus; Desiana, Putri Mega; Ahyinaa, Gyandra Sekar (Universitas Airlangga, 2025)
Objective: This study aims to investigate the potential moderating effects of toxic leadership on employee turnover intention. The study also investigates the impact of internal social media usage on employee engagement. Design/Methods/Approach: The data for this study consisted of 305 employees, whose information was obtained through online questionnaires. The collected data was then analyzed employing the Structural Equation Model (SEM) using Lisrel 8.8 software. Findings: The findings of this study provide evidence that toxic leadership acts as a moderator in the relationship between internal social media usage and turnover intention. Also, employee engagement acts as a mediator in the relationship between internal social media usage and toxic leadership to turnover intention. Originality/Value: This study builds on previous research on social exchange theory by exploring the connections between internal social media usage and employee engagement, while uniquely examining the moderating role of toxic leadership, an aspect not fully addressed in prior studies. Practical/Policy implication: Companies should leverage internal social media usage to boost employee engagement, which can significantly reduce turnover intention. By fostering better communication and collaboration, ISMU can lead to a more connected, satisfied, and committed workforce.